El Excentrico, 1962-03-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
March 20, 1962 [20 de marzo de 1962]. Ano 12, No 10. Cover has picture of a model named Rose Mary Gardillo, with headline. "Rose Mary Gardillo-newcomer to San Jose."